2021
DOI: 10.3389/fneur.2021.666632
|View full text |Cite
|
Sign up to set email alerts
|

Transient Global Amnesia (TGA): Influence of Acute Hypertension in Patients Not Adapted to Chronic Hypertension

Abstract: Objective: Transient global amnesia (TGA) is defined by an acute memory disturbance of unclear etiology for a period of <24 h. Several studies showed differences in vascular risk factors between TGA compared to transient ischemic attack (TIA) or healthy controls with varying results. This retrospective and cross-sectional study compares the cardiovascular risk profile of TGA patients with that of acute stroke patients.Methods: Cardiovascular risk profile and MR imaging of 277 TGA patients was retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…A recent study by our group showed an association between acute hypertension and TGA occurrence ( 10 ). Herein, TGA patients were less likely to suffer from chronic hypertension compared to acute stroke patients.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…A recent study by our group showed an association between acute hypertension and TGA occurrence ( 10 ). Herein, TGA patients were less likely to suffer from chronic hypertension compared to acute stroke patients.…”
Section: Discussionmentioning
confidence: 89%
“…These observations are substantiated by evidence of a lower vascular mortality risk in TGA patients compared with TIA patients ( 11 ). It was hypothesized that acute hypertensive peaks may trigger TGA episodes, especially in patients who are not adapted to chronic hypertension ( 10 ). These observations are well in line with our current results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations